Influence of pulsed Nd:YAG laser welding power on the microstructures and nano creep behaviour of Ti5Al2.5Sn beads. (May 2023) - Asif, Huzaifa; Khan, Fahd Nawaz; Shehbaz, Tauheed; Junaid, Massab; Baig, Mirza Nadeem
Pulsed Nd:YAG laser beam welding was performed at five different power levels (360 W, 380 W, 400 W, 420 W and 440 W), and the relationship between microstructure and nano creep behaviour was investigated for Ti5Al2.5Sn alloy. Microstructural analysis indicated a reduction in grain size in fusion zone, with an increase in the average laser power. In the fusion zone (FZ) of all the beads, acicular α and ά martensite were observed and confirmed by SEM analysis. Due to the formation of the α and ά phases during welding, the microhardness and nanohardness in the FZ increased by ∼71% and ∼58%, respectively, above that of the base alloy. Nano creep analysis suggested diffusional creep as the deformation mechanism in all the beads, except the one performed at an average power of 440 W since its stress exponent was less than 2.